La filosofía institucional y el liderazgo, en el desarrollo académico del colegio “8 de Diciembre”, de la parroquia San Pedro de la Bendita, cantón Catamayo, provincia de Loja, período 2012 – 2013 - Caraguay Caraguay, Luis (2014)
This research named INSTITUTIONAL PHILOSOPHY AND LEADERSHIP IN THE ACADEMIC DEVELOPMENT OF “8 DE DICIEMBRE” HIGH SCHOOL, IN SAN PEDRO DE LA BENDITA PARISH, CATAMAYO CANTON, LOJA PROVINCE. PERIOD 2012- 2013. As general objective include: to determine the effects of institutional philosophy and leadership in the academic development of the “ 8 de diciembre” high school in San Pedro de la Bendita parish, Catamayo canton, Loja province, period 2012- 2013. In the process of this research two specific objectives with corresponding hypotheses were structured, which were demonstrated by the theoreticaldeductive method helped by the descriptive statistics. The conceptual theoretical foundations compared to the empirical referents, conclude that even teachers and administrators ignore the components to structure the institutional philosophy of the school, demonstrating the lack of preparation on the vision, mission, policies, moral values, institutional leadership and teaching tools provided in the development of learning, therefore, teachers only care of meet workday neglecting academic levels of development. The work is complemented by presenting alternative guidelines, extended suggestions that enhance the originality and implementation of the corporate philosophy, ideological culture of democratic participation to improve the academic development of students.